Bible translations for the minorities" languages today: A biblical theological exploration - Rabali, Tshitangoni C. (HTS teologiese studies, 2021)
The contemporary world is a harsh environment for many languages and cultures. Globalisation is one of the powerful forces that are increasing the pressure on some languages to become extinct. The questions that, therefore, arise for Bible translation include: Does it still make sense to translate the Bible into languages that are being threatened by extinction? Are there perhaps certain indicators that should be present for the translation of the Bible into endangered languages to make sense and to possibly also contribute towards the revival of languages that are being threatened by extinction? The discussion of these and related questions is not new but has to continue because the issues can be viewed from a variety of angles. This article is offered as a biblical theological exploration of the issues. It is, therefore, also a biblical theological motivation for Bible translation into endangered languages. The article argues that the existence of a growing church that is committed to the use of the Bible in a particular translation should be viewed as one of the critical indicators when assessing the merits of such translation projects.Contribution: The primary contribution of this article is that it approaches the issues pertaining to language endangerment from a biblical theological angle; and demonstrates that the issues regarding language endangerment are connected to the core of the Bible’s message. Language endangerment is one of the results of Adam’s fall into sin. God’s redemptive work will end language endangerment when God’s gracious work of saving creation and fallen humanity is consummated at Christ’s return.